Aspects of growth, structural change, and employment: A Schumpeterian perspective - Herbert Giersch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1979)
This paper aims to throw some light on problems of growth and employment that appear to have been somewhat neglected in the recent development of mainstream economics. As the subtitle suggests we shall make use of a framework of thought that might be called Schumpeterian, in honor of Joseph Schumpeter, who taught in Vienna and Bonn as well as at Yale and Harvard, and who deserves - as some people here in Kiel think - more credit than he usually receives in the shadow of Keynes. This system of thought emphasizes - a medium run time horizon, as distinct from the Keynesian short run and the classical, neoclassical, or Marxian long run; - the cyclical nature of capitalist development, rather than the notions of short run or long run equilibrium, as a basic postulate; the catallactic features of activity in the private sector and hence the information and coordination problems arising in decentralized systems - in contrast to a view which Hicks calls plutologist or social accounting Keynesianism (Hicks 1976); - active or dynamic competition of all sorts (Schumpeter's creative destruction) among entrepreneurs, whom Schumpeter (1912) defined as everyone who carries out new combinations; - autonomy, spontaneity, curiosity, experimenting, and-risk taking as essentials of human action under competitive conditions in business as well as in research - in contrast to the notion of perfect competition and its implicit situational determinism (Latsis 1976); - supply activities rather than demand mechanics, such as demand induced (accelerator) investments or multiplier processes. This approach certainly is supply oriented, in contrast to the demand bias of short run macro-economics. Effective demand is taken to be a consequence (multiplier effect) of private supply activities, i.e. of autonomous investments. A shortfall of demand can be explained in this framework as a consequence of unfavorable conditions for autonomous investments, including - a shortage of technological breakthroughs, - a shortage of factors complementary to investments, - institutional constraints, - a shortage of entrepreneurs, and - a distortion of relative prices depressing profits and profit expectations.
Keywords: 330